Research progress of Bacillus velezensis in plant disease resistance and growth promotion - Zhong, Xianfeng; Jin, Yuying; Ren, Hong; Hong, Tingting; Zheng, Jianwei; Fan, Wenjing; Hong, Jiazhi; Chen, Ziqi; Wang, Ali; Lu, Huaiyu; Zhong, Kaijie; Huang, Guidong (Frontiers in Industrial Microbiology, 2024)
Bacillus velezensis has a wide range of beneficial activities, such as fighting plant diseases, promoting growth, improving crops’ ability to handle stress, and boosting plant defenses. These traits make it a strong candidate for agricultural use, especially as a biocontrol agent and growth-promoting bacteria. This review takes a close look at the origins, working mechanisms, and potential agricultural benefits of B. velezensis. Both lab and field studies have shown its success in reducing plant diseases and supporting crop growth by producing helpful compounds, taking up space in the environment, and strengthening plant defenses. Although B. velezensis is already used in some fertilizers and biopesticides, there are still challenges in scaling up production, selecting the right strains, and ensuring product stability. This review points out current research gaps and suggests future directions, such as improving strain selection, developing better biofertilizers, and advancing production techniques to make the most of B. velezensis in agriculture. These findings aim to guide further research and improve its use in sustainable farming.